2004
DOI: 10.1111/j.1654-1103.2004.tb02279.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed vegetation of arable land in Central Europe: Gradients of diversity and species composition

Abstract: Question: What are the main broad‐scale spatial and temporal gradients in species composition of arable weed communities and what are their underlying environmental variables? Location: Czech Republic and Slovakia. Methods: A selection of 2653 geographically stratified relevés sampled between 1954–2003 was analysed with direct and indirect ordination, regression analysis and analysis of beta diversity. Results: Major changes in weed species composition were associated with a complex gradient of increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
144
5
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 24 publications
21
144
5
6
Order By: Relevance
“…Contrastingly, we found a higher species richness in the less productive areas where the intensification factors were not as highly employed. Our results confirm the findings of Lososová et al (2004) and Fried et al (2008), who also recorded higher species richness in agrophytocoenoses at higher altitudes.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Contrastingly, we found a higher species richness in the less productive areas where the intensification factors were not as highly employed. Our results confirm the findings of Lososová et al (2004) and Fried et al (2008), who also recorded higher species richness in agrophytocoenoses at higher altitudes.…”
Section: Resultssupporting
confidence: 82%
“…The results of this study endorse the findings of Fried et al (2008), who also indicated a reduction in β-diversity at higher altitudes (> 300 m) and with extreme soil pH (acidic or alkaline) or on sandy soils. Lososová et al (2004) also reported a clear decrease in β-diversity with increasing altitude. As for individual crops under conventional and organic farming, greater β-diversity was recorded for the root crops and winter cereals, respectively (Figure 3).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As an alternative, a national system of plant indicators was developed by Jurko (1990). Nevertheless, EIVs have been widely used by many authors in Slovakia, and in numerous fields of environmental and ecological science (e.g., Lososová et al 2004;Uherčíková & Némethová 2006;Janišová et al 2010;Chovancová & Križová 2010). The two main aspects of the criticism are addressed in this study: (i) Ellenberg's R indicator values should be validated for a particular region, and (ii) calibration to physical pH measurements can significantly increase performance of plant indicator systems (e.g., Lawesson et al 2003;Wamelink et al 2005).…”
Section: Discussionmentioning
confidence: 99%